Representation of Sensory Perceptions and Emotional Responses in the Language of Literary Texts - Koliada, Elina; Kalynovska, Iryna (Lesya Ukrainka Volyn National University, 2023)
The article is dedicated to the literary description of sensory perceptions and emotional responses. The article's authors treat the latter as an effect of perceptual processes. Information about the world is acquired through the senses. Our most common folk model of the senses emphasizes the distinctiveness of each of the five senses (sight, hearing, taste, smell, and touch) by its relation to a distinctive organ of the body. Literary narratives excel at depicting how our senses interact and provide correlated information about the world, with one sensory perception influencing and enriching another. The examples taken from literary texts illustrate visual perception, auditory perception, gustatory perception, olfactory perception, and tactile perception. By engaging multiple senses, writers create a richer, more engaging experience. Descriptions of how characters perceive the world around them reveal their personalities and emotional states.Writers rely heavily on declarative sentences and sensory vocabulary to effectively describe characters’ sensory perceptions. Declarative sentences convey a sense of certainty and firsthand experience, immersing the reader directly in the scene. They stateobservations clearly and emphasize key details. Sensory vocabulary (language that describes things related to the five senses) helps writers create vivid descriptions. By using words that evoke sight, sound, smell, taste, and touch, writers bring the depicted scenes to life. Precise sensory details create a unique and memorable image in the reader’s mind, allowing them to participate in the sensory experience, forming a deeper connection with the narrative.
Keywords: sight; hearing; taste; smell; touch; emotional response; literary text; 811.111’23